Toxic gain of function from mutant FUS protein is crucial to trigger cell autonomous motor neuron loss. (8th March 2016) - Scekic‐Zahirovic, Jelena; Sendscheid, Oliver; El Oussini, Hajer; Jambeau, Mélanie; Sun, Ying; Mersmann, Sina; Wagner, Marina; Dieterlé, Stéphane; Sinniger, Jérome; Dirrig‐Grosch, Sylvie; Drenner, Kevin; Birling, Marie‐Christine; et al.
Abstract: FUS is an RNA‐binding protein involved in amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Cytoplasmic FUS‐containing aggregates are often associated with concomitant loss of nuclear FUS. Whether loss of nuclear FUS function, gain of a cytoplasmic function, or a combination of both lead to neurodegeneration remains elusive. To address this question, we generated knockin mice expressing mislocalized cytoplasmic FUS and complete FUS knockout mice. Both mouse models display similar perinatal lethality with respiratory insufficiency, reduced body weight and length, and largely similar alterations in gene expression and mRNA splicing patterns, indicating that mislocalized FUS results in loss of its normal function. However, FUS knockin mice, but not FUS knockout mice, display reduced motor neuron numbers at birth, associated with enhanced motor neuron apoptosis, which can be rescued by cell‐specific CRE‐mediated expression of wild‐type FUS within motor neurons. Together, our findings indicate that cytoplasmic FUS mislocalization not only leads to nuclear loss of function, but also triggers motor neuron death through a toxic gain of function within motor neurons. Synopsis: Truncation of FUS, leading to cytoplasmic mislocalization, as well as loss of FUS leads to perinatal lethality in mice and alterations in RNA expression and splicing. However, only FUS cytoplasmic mislocalization triggers motor neuron degeneration through motor neuron intrinsic toxicity. Cytoplasmic FUS mislocalization leads to perinatal death and motor neuron degeneration in knockin mice. Complete loss of FUS leads to perinatal death in the absence of motor neuron degeneration. Cytoplasmic FUS mislocalization leads to alterations in gene expression and RNA splicing partially overlapping with complete loss of FUS. Selective rescue of cytoplasmic FUS mislocalization in motor neurons prevents motor neuron degeneration, but not perinatal death. Abstract : Cytoplasmic accumulation of ALS‐associated FUS mutants not only leads to nuclear loss‐of‐function phenotypes, but also to motor neuron degeneration via toxic gain‐of‐function mechanisms.